Improvement of family-centered care in the pediatric rehabilitation ward: a participatory action research - Nematifard, Taban; Arsalani, Narges; Nourozi Tabrizi, Kian; Fallahi-Khoshknab, Masoud; Borimnejad, Leili (Frontiers in Pediatrics, 2024)
The improved life expectancy of children with disability in recent years has led to their increased request for using lifelong rehabilitation services. Familycentered care (FCC) is a model with potential positive effects on the rehabilitation of children with disability. The present study aimed at improving FCC in the pediatric rehabilitation ward. Methods: This participatory action research was conducted in 2021-2023 in the pediatric rehabilitation ward of a hospital in Tehran, Iran. Participants were 16 rehabilitation staff and 48 mothers recruited via convenient and purposive sampling methods. Data were collected using semi-structured interviews, focus group discussions, and the 20-item and the 27-item Measures of the Processes Of Care (MPOC). Data were analyzed using qualitative content analysis as well as the Kolmogorov-Smirnov and the Wilcoxon's tests. Findings: The major barrier to the implementation of FCC was staff and family limited knowledge about the importance and the benefits of FCC and the best facilitator to change was improvement of their knowledge. Therefore, an action plan based on staff and family education was designed and implemented. Participants' positive experiences of the plan were improvement of satisfaction, knowledge, collaboration, and coordination in care and their negative experiences were educational problems and dissatisfaction with the ward atmosphere. The strengths of the plan were adequate number of staff, long enough hospital stay of children, chronic course of disability, and mothers' previous experiences. Its weaknesses were the long course of a single action plan cycle, exclusive focus on education, and the high risk of plan termination after the study. The practical problems of the study were also small physical space of the ward, transfer of some trained staff to other wards, and child discharge from the hospital. Conclusion: Staff and family limited knowledge about the importance and the benefits of FCC is a major barrier to effective FCC. Continuous education as well as family and staff collaboration may improve FCC in pediatric rehabilitation ward.